Closure of Orocutaneous Fistula Using Submandibular Gland as a Pedicled Flap - Erol Cansiz; Emine Deniz Gozen; Murat Yener (Case Reports in Dentistry)
Orocutaneous fistulas in the maxillofacial region may be due to tumor resection, osteoradionecrosis, or trauma, and these defects limit the function of the patients and effect aesthetic and also psychological condition. Articulation and nutrition are also affected by these fistulas. Local flaps can be used for the reconstruction of small- and medium-sized defects with ease. Submandibular gland with its rich blood supply from the facial artery is a practical and useful choice for the reconstruction of mandibular region defects.